Determination of Life Microinsurance Premium Using the Commercial Rate Method - Azizah Rini Widyani; Riaman Riaman; Sukono Sukono (Research Collaboration Community (RCC), 2023)
Microinsurance is insurance that is intended for people who have low incomes which is made with the aim that all levels of society can have insurance with affordable prices. Life insurance is a protection program for families in the event of unwanted things, such as death or permanent disability, to policy holders. This study aims to determine the life microinsurance premium. The data sample used is data on claim and benefit paid by life insurance company obtained from the official website of Otoritas Jasa Keuangan (OJK) Indonesia, which is assumed to have a log-normal distribution. The research method is to test the distribution of claims from the sample data using the Kolmogorov-Smirnov test. Then determine the value of the claim distribution parameter, and then calculating life microinsurance premium using the Commercial Rate method. The results obtained in the form of premium for life microinsurance that are payable by low-income people.